UNDERSTANDING WELLNESS TOURISM MOTIVATION IN INDIA: A CROSS-CULTURAL VALIDATION OF THE WELLNESS TOURISM MOTIVATION SCALE (WTMS) - DHILLON, PARMINDER SINGH (Revista de turism - studii și cercetări în turism, 2025)
Wellness tourism is a rapidly growing sector in the global travel industry, and India has emerged as a significant player in this market. This study aimed to validate the Wellness Tourism Motivation Scale (WTMS) in the Indian context, as understanding tourists' motivations for engaging in wellness travel is vital for both the industry and destination marketing. The WTMS is a well-established instrument used to assess tourists' motivations for participating in wellness-related activities during their trips. A total of 634 Indian wellness tourists were surveyed in top five wellness destinations within India. The sample was distributed in two groups to conduct EFA and CFA. The findings indicate that the WTMS exhibits strong reliability and validity when applied to the Indian wellness tourism context. The scale's factor structure was consistent with previous research, identifying various motivation factors. This research contributes to the growing body of knowledge on wellness tourism in India, fostering its sustainable growth and global competitiveness. The implications are discussed in details.